Robert Zaretsky. A Life Worth Living: Albert Camus and the Quest for Meaning. Cambridge, Mass., and London: The Belknap P of Harvard UP, 2013. 240 pp. - Melissa M. Ptacek (Studies in 20th & 21st Century Literature, 2015)
Review of Robert Zaretsky. A Life Worth Living: Albert Camus and the Quest for Meaning. Cambridge, Mass., and London: The Belknap P of Harvard UP, 2013. 240 pp.
Keywords: Albert Camus